THE MORAL VALUES CONTAIN IN FORREST GUMP MOVIE. - Sari, Noviani Radna; Maisarah, Ira (Universitas Gunadarma, 2024)
A movie is a form of media used to communicate messages and information. It also serves as a medium for learning. The moral values represented in movies can be identified. Hence, this study aimed to investigate the moral values presented in the Forrest Gump movie. The current research employed a qualitative method. The researchers acquired the data from recordings of the Forrest Gump movie. The findings indicate that the Forrest Gump movie encompasses various moral values, including individual moral values, social moral values, and moral values about the human relationship with God. The categories of individual moral values include courage, humility, diligence, perseverance, goodness, and tolerance. The social moral values can be categorized as collaboration, helpfulness, affection, and care. The moral values about the human relationship with God include religiousness, gratitude, sincerity, and recognition of the greatness of God. The Forrest Gump movie encompasses a set of moral values. Ultimately, we can implement moral principles in our everyday existence. An ethical principle derived from the movie is the demonstration of affection and care. It is recommended that humans should prioritize the well-being of our children, parents, and friends. People should not participate in discrimination against individuals with disabilities.